Spiritual Contributions of TGH. Ibrahim Al-Khalidy’s Prayer to SDGs Achievement on Lombok Island - Abdul Kohar (Universitas Muhammadiyah Surakarta, 2025)
Objective: The purpose of this study is to analyze the algorithm for the preparation of the Prayer Schedule Throughout the Lifetime by TGH. Ibrahim al-Khalidy, evaluated its relevance, as well as tested its accuracy. Theoretical framework: The theoretical framework used includes normative-empirical studies based on astronomy and modern astronomical methods, which combine religious approaches with contemporary scientific approaches. Literature review: The literature review in this study refers to books and journals related to astronomy, prayer time hisab methods, and integration between traditional and modern knowledge. Methods: The method used is a normative-empirical qualitative approach, with primary data in the form of a prayer schedule prepared interviews with the drafting team, and secondary data from related literature. The analysis was carried out by comparing the method of calculating the TGH prayer time. Ibrahim al-Khalidy with modern astronomical methods, as well as accuracy testing through 300 times prayer time calculations in various areas of Lombok on certain dates from 2016 to 2020. Results: The results showed that the schedule had a time deviation of 69% delay and 31% acceleration, with the largest deviation in the time of Isha in East Lombok (5 minutes 39 seconds) and Maghrib in Mataram (3 minutes 46 seconds). Implications: The implication of this study is the importance of updating astronomical data and refining calculation algorithms to make the schedule more accurate and by the current astronomical conditions, while still maintaining the spiritual and cultural values contained in it. Novelty: The novelty of this research lies in the combination of traditional astronomy with modern astronomical methods in the evaluation of local prayer schedules, as well as its contribution to the achievement of the Sustainable Development Goals (SDGs) through the preservation of local knowledge, the strengthening of cultural identity, and the promotion of the spiritual well-being of the community.